BEBERAPA FAKTOR YANG MEMPENGENGARUHI RENCANA PEMBERIAN ASI EKSKLUSIF PADA REMAJA PUTRI DI WILAYAH KERJA PUSKESMAS PEGANDAN KOTA SEMARANG - Astrid Ayu Utami; Syamsul Huda BM; Anung Sugihantono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Exclusive breast feeding is breast feeding the baby purely from age 0-6 months. Babies only can be feed with breast milk except medicine and vitamin. Based on the research there is 164 respondents (98,8%) that having a plan to give breast milk exclusively, there is respondents who have a plan to give breast feeding exclusively strong (55,4%), while the other (44,6%) are realtively weak. The formulation of the problem in this research is to understand some factors that affect the perceptions of giving exclusive breastfeeding for teenage girls.The purpose of this research is to analize some factors that affect the perception of exlclusive breastfeeding. Subject in this research is teenage girls who are included in the late teen age that between 18-21 years old who live in the working area of Pegandan Health Center Semarang with total of 166 respondents. The method of collecting the data is by using quetionnaires and interviews person to person.Data analysis technique that is used is chi square test. Based on the result of chi square analysis is obtained the perceived threat (p=0,000), perceived benefit (p=0,000), and perceived barrier(p=0,002). Those variables have p (<0,01), it means that there is a positive relation between those variables with the perception of exclusive breastfeeding plan. While for the variables that most influence is the perceived benefit with OR of 6,711. The conclusion of this research is there is positive relation between perceived threat, perceived benefit, and perceived barrier, and the most influence is perceived benefit with the perception of exclusive breast feeding plan among teenage girl in the working area of Pegandan Health Center Semarang City.